Studi Intelektual tentang Penyebaran Islam di Nusantara dalam Pemikiran Azyumardi Azra - Istiqomah Istiqomah; Rachmat Panca Putera; Muhammad Zamzam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines Azyumardi Azra’s interpretation of Islamization in the Malay-Indonesian Archipelago, highlighting its significance in both historical and contemporary discourse. Using a qualitative library research approach, the analysis draws on Azra’s key works, especially The Ulama Network: Southeast Asia and the Middle East in the Seventeenth and Eighteenth Centuries, and is supported by recent scholarly literature. Azra challenges conventional theories that attribute Islamization mainly to trade, political authority, or intermarriage. Instead, he underscores the central role of ulama networks, the transmission of religious knowledge, and the influence of Sufism. His perspective reveals how intellectual chains connected Southeast Asian scholars to Middle Eastern centers of learning, particularly Mecca and Medina, thus situating Islam in the archipelago as an integral part of global Islamic scholarship. Furthermore, Azra emphasizes the adaptive and dialogical character of Islamization, whereby Islamic teachings were internalized through cultural accommodation, shaping the distinctive identity of Islam Nusantara as moderate, inclusive, and cosmopolitan. The findings suggest that Azra’s framework not only advances historiography but also contributes to contemporary debates on religious moderation and Indonesian Islamic identity. This study concludes that his intellectual model provides a valuable foundation for further research that incorporates social, political, and economic dimensions of Islamization.